2008
DOI: 10.1159/000121370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Housing Characteristics and Home Environmental Factors on Respiratory Symptoms of 10,784 Elementary School Children from Northeast China

Abstract: Background: Only few studies have assessed the relative impact of housing characteristics and home environmental factors on asthma and asthma-related symptoms in Chinese children, and to our knowledge, few studies have elaborated respiratory symptoms and allergies in this context. Objective: It was the aim of this study to assess the effects of housing characteristics, pet keeping, home decorations and other indoor environmental factors on respiratory health of Chinese children. Methods: We studied 10,784 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 82 publications
2
22
0
2
Order By: Relevance
“…This finding was consistent with the cross-sectional study of 14077 Swedish children aged 1-6 years, which reported four "dampness" indices including visible molds and windowpane condensation were associated with children's asthma, rhinitis and eczema symptoms [21]. In China, Dong et al [22][23][24] reported that signs in the home of water damage or visible mold on walls were positively associated with children's asthma symptoms in preschool children and elementary children in northeastern area of China. A recently published 10-year longitudinal study of adults in Uppsala, Sweden, found that signs of dampness in floor construction of any workplace building during follow up (cumulative exposure) were associated with incidence of mucosal symptoms (OR=2.43) including nasal catarrh, nasal obstruction, dryness in throat, sore throat or irritating cough [25].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding was consistent with the cross-sectional study of 14077 Swedish children aged 1-6 years, which reported four "dampness" indices including visible molds and windowpane condensation were associated with children's asthma, rhinitis and eczema symptoms [21]. In China, Dong et al [22][23][24] reported that signs in the home of water damage or visible mold on walls were positively associated with children's asthma symptoms in preschool children and elementary children in northeastern area of China. A recently published 10-year longitudinal study of adults in Uppsala, Sweden, found that signs of dampness in floor construction of any workplace building during follow up (cumulative exposure) were associated with incidence of mucosal symptoms (OR=2.43) including nasal catarrh, nasal obstruction, dryness in throat, sore throat or irritating cough [25].…”
Section: Discussionsupporting
confidence: 86%
“…Home decoration and building materials have been reported in relation with children's respiratory symptoms in different areas in the world [24,31,32]. In this study, floors surfaced by wood, PVC or carpeting (totally accounting for 44.7%); or walls surfaced by wood, wallpaper or painting (totally accounting for 80.7%), were common, and were both positively associated with children's AR symptoms in the last 12 months.…”
Section: Discussionmentioning
confidence: 66%
“…DIJKSTRA [29] DALES [16] DALES [32] PONSONBY [18] ZHENG [27] CHEN [25] FREEMAN [20] FREEMAN substudy [20] SPENGLER [19] PEKKANEN [33] DONG [17] DONG [22] ANTOVA [15] WARMAN [24] Summary (OR FAGBULE [34] VERHOEFF [31] LI [26] LI [35] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] BRUNEKREEF [21] STRACHAN [37] STRACHAN [38] DIJKSTRA [29] DALES [16] SPENGLER [19] EMENIUS [36] ALPER [39] DONG [17] DONG [22] ANTOVA [15] ROSENBAUM [43] IOSSIFOVA [8] KARVONEN [42] Summary (OR LI [26] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] CHEN [25] BIAGINI [45] IBARGOYEN-ROTETA [44] KOSKINEN substudy [47] KOSKINEN [47] LI [26] LI [35] BRUNEKREEF [21] DONG …”
Section: Discussionmentioning
confidence: 99%
“…Two Asian studies from Singapore also reported higher risks for rhinitis and rhinoconjunctivitis among 1-12-yr-old children [25,65]. The remaining six studies did not observe any statistically significant exposure-response relationships [17,22,26,44,47].…”
Section: Allergic Rhinitismentioning
confidence: 91%
“…However, the average prevalence of diagnosed asthma has increased in each province in the last two decades [2]. Air pollutants, western life style factors, home environment, allergens, heredity, personal growing environment and diet have all been investigated in relation to children's asthma or allergic diseases in Chinese children [3][4][5]. Prenatal exposure and early life factors have been less thoroughly studied [6].…”
mentioning
confidence: 99%